Investigating Macular Tissue Integrity Index as a Novel Biomarker in Geographic Atrophy - Bethany M. Erb, MD; Elaine Botros; Thomas F. Saunders, OD; Anna-Maria Haas, MD; Rick Voland, PhD; Rachel Linderman, PhD; Amitha Domalpally, MD, PhD; Karl G. Csaky, MD (Ophthalmology Science)
Purpose: The rate of geographic atrophy (GA) enlargement is commonly used as an outcome in clinical trials. However, this metric typically lacks specificity for central macular involvement and structure–function relationships. We propose a targeted approach in monitoring GA progression within the central macula, highlighting the limited benefit of including GA expansion beyond the 3-mm perifoveal zone when analyzing visual function. This study evaluates how retinal tissue and photoreceptor integrity within the central 1-mm and 3-mm circles centered on the fovea correlate with visual function. Design: Retrospective, longitudinal analysis of a GA clinical trial cohort. Subjects: Forty-three eyes from 43 participants enrolled in GA clinical trials. Methods: Baseline and 1-year fundus autofluorescence (FAF) and OCT scans were analyzed. The percentages of non-GA areas within the 1-mm and 3-mm circles centered on the fovea were quantified to calculate the Macular Tissue Integrity Index (MTII) using FAF images. The percentages of intact ellipsoid zones within the same circles were used to define the EZ Integrity Index (EZII). Longitudinal changes in MTII and EZII were compared to overall GA area growth and change in visual acuity (VA). Main Outcome Measures: Correlations between MTII, EZII, GA area, and VA (best-corrected VA [BCVA] and low-luminance VA [LLVA]) were assessed. Results: Macular Tissue Integrity Index and EZII within the central 1 mm correlated significantly with BCVA (R2 = 0.20, P = 0.003 and R2 = 0.29, P < 0.001, respectively), while EZII in the 3-mm zone correlated with both BCVA and LLVA (R2 = 0.17, P < 0.01 for both). Changes in MTII or EZII over time were not associated with GA area growth or with baseline integrity indices. Conclusions: Macular Tissue Integrity Index and EZII are novel biomarkers for macular photoreceptor integrity, with distinct correlations to BCVA and LLVA depending on the measurement zone. These findings support the utility of MTII and EZII in assessing macular integrity and highlight the heterogeneity of GA progression, warranting further validation in larger studies.